2009
DOI: 10.26719/2009.15.2.455
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of animal bites in Rafsanjan, southeast of Islamic Republic of Iran, 2003-05

Abstract: The incidence of animal bites in the Islamic Republic of Iran has been increasing in recent years. In a descriptive study of 1542 patients referred to a health centre in Rafsanjan city from 2003 to 2005, the incidence of animal bites in the area was estimated as 180, 195 and 241 per 100 000 in 2003, 2004 and 2005 respectively. Of the patients, 74% were bitten by dogs, 23% by cats and 3% by other animals (monkeys, rats, foxes, bats, donkeys, etc.). The mean time delay from injury to initial management was 15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 2 publications
4
25
0
Order By: Relevance
“…A research in Tehran showed that among 8806 patients treated for animal bites, 94% were from Tehran city and 6% from the suburbs (11). In Rafsabjan, 45% of animal bites occurred in urban areas, while 55% were reported in rural areas (17). However, in Ilam 77.3% of patients were rural inhabitants, while 22.7% were living in the city (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A research in Tehran showed that among 8806 patients treated for animal bites, 94% were from Tehran city and 6% from the suburbs (11). In Rafsabjan, 45% of animal bites occurred in urban areas, while 55% were reported in rural areas (17). However, in Ilam 77.3% of patients were rural inhabitants, while 22.7% were living in the city (15).…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance host is dominantly a domestic dog or a wild animal species (19). Several cases of animal bite are reported in Iran (11) and its frequency has been rising in recent years (17). Out of 2783 exposed cases referred to public health centers for animal bites, from April 2006 to September 2011 in Borujerd, the biting animals were mostly dogs, cats, fox and wolf, sheep and cow, monkey and donkey, mouse and squirrel and also other animals with 69.8%, 17.2%, 1.4%, 2.8%, 5%, 2.2% and 1.6% respectively (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11). There are also other epidemiological studies, which have reported increase in the incidence of animal rabies in Iran (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Rabies disease exists in Iran for a long time and it is endemic in the country (4). Incidence of animal bites is increasing in different parts of Iran in the recent decades (5)(6)(7)(8). In addition, dogs are the main reservoir of the disease and all rabies cases reported in Iran were associated with dog bites often poorly controlled (4).…”
Section: Introductionmentioning
confidence: 99%